2011
DOI: 10.1177/039463201102400128
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Deficiencies in a Consecutive Series of Children with Herpetic Encephalitis

Abstract: Natural killer (NK) cells play a fundamental role in innate and early phases of adaptive immunity against viral infections, both in humans and in animal models. To date, NK cell deficiencies in patients with severe herpetic infections have been reported in single cases, and their role as predisposing factor is still controversial. Five children affected by herpetic encephalitis were consecutively admitted to the Anna Meyer Children's Hospital in Florence (Italy) between 2003 and 2005. We therefore investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
(23 reference statements)
0
23
0
2
Order By: Relevance
“…Shortly after they were discovered, NK cells were shown to play an important role in antiviral immune responses. The rare patients completely devoid of NK cells were extremely susceptible to infections by viruses of the herpes family (26,27). Five consecutive children with herpetic encephalitis were shown to have functional NK cell deficiencies (27).…”
Section: Nk Cell Modifications Associated With Cns Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortly after they were discovered, NK cells were shown to play an important role in antiviral immune responses. The rare patients completely devoid of NK cells were extremely susceptible to infections by viruses of the herpes family (26,27). Five consecutive children with herpetic encephalitis were shown to have functional NK cell deficiencies (27).…”
Section: Nk Cell Modifications Associated With Cns Disordersmentioning
confidence: 99%
“…The rare patients completely devoid of NK cells were extremely susceptible to infections by viruses of the herpes family (26,27). Five consecutive children with herpetic encephalitis were shown to have functional NK cell deficiencies (27). By using a mouse model of HSV1 encephalitis, Adler et al (28) directly demonstrated that NK cells have an important role in the defense against this severe form of infection.…”
Section: Nk Cell Modifications Associated With Cns Disordersmentioning
confidence: 99%
“…For herpesviruses in particular, functional NK cells are crucial for limiting virus spread and disease symptoms. Indeed, impaired NK cell activity has been associated with life-threatening encephalitis caused by the human alphaherpesviruses herpes simplex virus 1 (HSV-1) and varicellazoster virus (VZV) (2)(3)(4). Given the strong antiviral potential of NK cells against herpesviruses in particular, it comes as no surprise that several herpesvirus strategies for evading NK cells have been discovered (5).…”
mentioning
confidence: 99%
“…Functional NK cells are of particular importance in preventing herpesviruses from causing aggravated disease, including life-threatening encephalitis for alphaherpesviruses like HSV and varicella-zoster virus (1)(2)(3). The significance of the NK cell response against herpesviruses is also reflected by the various mechanisms that these pathogens have evolved to evade or delay it (4).…”
mentioning
confidence: 99%